Dual recognition of H3K4me3 and H3K27me3 by a plant histone reader SHL - Shuiming Qian (Nature Portfolio, 2018)
Histone mark reader proteins bind to particular histone modifications and regulate chromatin state. Here, Qian et al. show that the SHORT LIFE reader has a unique ability to recognize both activating and repressive histone marks and that these interactions enable SHORT LIFE to repress flowering in plants.